2018
DOI: 10.1253/circj.cj-17-1275
|View full text |Cite
|
Sign up to set email alerts
|

Rural-Urban Disparity in Emergency Care for Acute Myocardial Infarction in Japan

Abstract: AMI patients in rural areas were less likely to be transported directly to PCI-capable facilities, resulting in time delay to PPCI compared with those in metropolitan areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“…In this context, Masuda et al recently reported that AMI patients in rural areas were less likely to be transported directly to PCI-capable facilities, resulting in longer time from onset to PCI, compared with those in metropolitan areas. 6 The present study conducted by Matsuzawa et al 1 also suggests higher in-hospital mortality rates among AMI patients who live in areas with lower population density than for those who live in high-…”
supporting
confidence: 55%
“…In this context, Masuda et al recently reported that AMI patients in rural areas were less likely to be transported directly to PCI-capable facilities, resulting in longer time from onset to PCI, compared with those in metropolitan areas. 6 The present study conducted by Matsuzawa et al 1 also suggests higher in-hospital mortality rates among AMI patients who live in areas with lower population density than for those who live in high-…”
supporting
confidence: 55%
“…The design of the study and its main results have been published previously. 9 Briefly, the Rural AMI Registry study prospectively enrolled patients with AMI who were hospitalized within 7 days from onset between January 2013 and March 2014; 41 hospitals in Japan took part in the study. In the present study, the diagnosis of AMI was based on the third universal definition of myocardial infarction (MI).…”
Section: Study Populationmentioning
confidence: 99%
“…However, pre-hospital 12-lead ECG was not officially introduced to the local EMS in Saitama City during the study period. There were significant differences in the quality of care for patients with AMI between rural areas and metropolitan areas [ 22 ]. Our results may not be applicable to other areas in Japan, because our results could be justified only when equivalent pre-hospital judgments are made by the EMS providers in the other areas.…”
Section: Discussionmentioning
confidence: 99%